Pengaruh Rasio Keuangan terhadap Financial Distress Sebelum dan Saat Covid-19 pada Perusahaan di Sektor Healthcare yang Terdaftar di Bursa Efek Indonesia - Pratama, Dominico Berta Kevin; Sari, Martdian Ratna (Research Center and Case Clearing House (RC-CCH) - Sekolah Tinggi Manajemen PPM, 2023)
This study aims to determine the effect of the liquidity, profitability, and solvency ratios on financial distress and the difference in financial distress before and during Covid-19 in companies engaged in the healthcare sector listed on the Indonesia Stock Exchange. The analysis method used in this study, descriptive analysis, classical assumption test, regression analysis test, and hypothesis testing processed using SPSS using a sample of 13 companies by taking the 2018-2021 financial report period, where 2018-2019 is the period before Covid-19 and 2020-2021 is the period during Covid-19. The calculation model carried out by researchers using the Zmijewski X-Score provides results that there is a significant negative effect on the current ratio, a significant negative impact on the return on asset ratio, a significant positive effect on the debt to asset ratio, and there is no difference in financial distress before and during Covid-19. This gives companies a lot of consideration in making decisions because if they make the wrong decision during a pandemic, the company will be closer to bankruptcy.